A 5-fluorouracil-loaded floating gastroretentive hollow microsphere: development, pharmacokinetic in rabbits, and biodistribution in tumor-bearing mice - Huang Y; Wei YM; Yang HR; Pi C; Liu H; Ye Y; Zhao L (Dove Medical Press, 2016)
Yu Huang,1,* Yumeng Wei,1,* Hongru Yang,2 Chao Pi,1 Hao Liu,1 Yun Ye,1,3 Ling Zhao1 1Department of Pharmaceutical Sciences, College of Pharmacy, Sichuan Medical University, 2Department of Oncology, 3Department of Pharmacy, The First Affiliated Hospital of Sichuan Medical University, Luzhou, People’s Republic of China *These authors contributed equally to this work Abstract: 5-Fluorouracil (5-FU) was loaded in hollow microspheres to improve its oral bioavailability. 5-FU hollow microspheres were developed by a solvent diffusion–evaporation method. The effect of Span 80 concentration, ether/ethanol volume ratio, and polyvinyl pyrrolidone/ethyl cellulose weight ratio on physicochemical characteristics, floating, and in vitro release behaviors of 5-FU hollow microspheres was investigated and optimized. The formulation and technology composed of Span 80 (1.5%, w/v), ether/ethanol (1.0:10.0, v/v), and polyvinyl pyrrolidone/ethyl cellulose (1.0:10.0, w/w) were employed to develop three batch samples, which showed an excellent reproducibility. The microspheres were spherical with a hollow structure with high drug loading amount (28.4%±0.5%) and production yield (74.2%±0.6%); they exhibited excellent floating and sustained release characteristics in simulated gastric and intestinal fluid. Pharmacokinetic studies demonstrated that 5-FU hollow microspheres significantly enhanced oral bioavailability (area under curve, [AUC](0-t): 12.53±1.65 mg/L*h vs 7.80±0.83 and 5.82±0.83 mg/L*h) with longer elimination half-life (t1/2) (15.43±2.12 hours vs 2.25±0.22 and 1.43±0.18 hours) and mean residence time (7.65±0.97 hours vs 3.61±0.41 and 2.34±0.35 hours), in comparison with its solid microspheres and powder. In vivo distribution results from tumor-bearing nude mice demonstrated that the animals administered with 5-FU hollow microspheres had much higher drug content in tumor, plasma, and stomach at 1 and 8 hours except for 0.5 hours sample collection time point in comparison with those administered with 5-FU solid microspheres and its powder. These results suggested that the hollow microspheres would be a promising controlled drug delivery system for an oral chemotherapy agent like 5-FU. Keywords: hollow microspheres, polyvinyl pyrrolidone, ethyl cellulose, pharmacokinetics, distribution, 5-fluorouracil